Validitas Pengembangan Soal Matematika Level 4 Model PISA Menggunakan Konteks Covid-19 - Maha Reihani; Muhammad Win Afgani; Retni Paradesa; Agustiany Dumeva Putri (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2020)
Creating and developing PISA model math problems using contexts with situations and conditions in everyday life can expand students' thinking in solving these problems. The aim of the author in conducting this research is to produce a PISA model mathematical problem using a valid Covid-19 context. This study involved two expert reviews, six peers, and three grade IX students of private junior high schools in Palembang as one-to-one research subjects. The research method used is a design research type of development study. Data collection techniques consisted of documentation, walk-throughs, tests, and interviews. The developed questions consist of one item. The results of the study stated that the questions developed were valid in terms of content, construct, and language by experts and colleagues. The question instrument has also been tested on students at the one-to-one stage to see its validity and from the one-to-one stage the questions are declared valid, it can be seen from students who can understand the purpose of the questions, are able to make assumptions and make related settlement plans so that can produce the correct answer.